Development of 3D Printing Filaments from Industrial Waste Plastics - Vijay Gupta; Arpit More; Chirag Sanghani; Rakesh Patel (International Journal of Energy and Thermal Applications, 2025)
The global plastic waste crisis has prompted innovative approaches to sustainable material reuse, particularly in additive manufacturing. Simultaneously, the accumulation of plastic waste presents significant environmental concerns. Recycling plastic into filament supports eco-friendly innovation and brings us closer to a circular economy where materials are reused instead of thrown away. This study investigates the development of 3D printing filaments from industrial waste plastics, including polypropylene (PP), acrylonitrile butadiene styrene (ABS), and nylon. The goal is to show how this method not only reduces waste but also makes 3D printing more affordable and sustainable. A custom-designed extrusion machine was developed and optimized to process these waste materials into filament, incorporating key components such as a hopper, barrel, lead screw, dual-heater system, cooling mechanism, and a variable frequency drive (VFD) for precise motor control. The methodology involved collecting, shredding, and drying industrial plastic waste before extrusion to achieve uniform filament quality. The study identifies key challenges in the filament production process, including material inconsistencies, extrusion temperature control, and filament dimensional stability. The findings demonstrate that recycled filament can be a viable alternative to virgin materials for additive manufacturing applications. This research contributes to sustainable 3D printing practices by offering an effective recycling approach and optimizing extrusion machine design for waste-based filament production. By integrating waste management with digital fabrication, this approach supports circular economy principles and presents a promising pathway toward sustainable manufacturing.
Keywords: 3D printing; ABS; Filament; Nylon; PP; plastic waste